Strategies in India since Independence: Planned Economy and Neo Liberalism: The Transformation of India's Economy from Planned Economy to Neo-liberalism (Journal of Advances and Scholarly Researches in Allied Education, 2019)
When India attained Independence in 1947, a changeover in the Indian economy was really long overdue to meet the difficulties of modernity. Right after increasing Independence the main challenges facing the Indian economy was modernisation and for that setting up of contemporary industries was experienced when the demand of the hour. India took to the road of economic planning for this after April one, 1951 influenced by the experience of the erstwhile Soviet economic planning like a number of other nations at that time of time. The report uses a number of vital commentary on India's neoliberalism conveyed in the type of the so-called New Economic Policy. It argues, New Economic Policy is actually a lot more when compared to a governmental policy. Neo-liberalism is actually applied through, as well as entails, the transformation of room, and hence creates overwhelming spatial unevenness. Neo-liberalism is as well a part of the imperialist task.